Estudo da inflamação e da autoimunidade na doença hepática gordurosa não alcoólica - Camargo, Karina Fernandes de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Obesity is characterized by excess fat within adipose tissue and other organs and it is closely linked to insulin resistance and other components of Metabolical Syndrome. Excessive fat in hepatocytes acts as an endocrine organ that releases inflammatory cytokines and increases the recruitment of lymphocytes (immune cells). When the immunological tolerance is reduced by this kind of stimulus, we can observe the development of autoimmune diseases. According to recent data, the lipids are specifically involved in the degradation of liver tolerance, but more studies are required to understand the interaction between fat, the immune system and steatosis. Our objective was to study the presence of inflammation and autoimmunity in non-alcoholic fatty liver disease (NAFLD) and verify whether the inflammation could represent a contributing factor to the markers of Autoimmune Hepatitis (AIH). This was an observational cross-sectional descriptive and prospective study. Fifty three individuals were included and submeted to medical and nutritional evaluation, biochemical tests and liver biopsy. The population was splitted in two groups for analysis: with AIH markers and without AIH markers. We found that 58.5% of the individuals had at least one type of antiautobody. There were no statistically significant differences between groups in the variables studied. By applying the International Group Autoimmune Hepatitis score (IGAIH), we found one case with a definitive diagnosis of AIH. We observed that body fat, waist and neck circumferences, while above the normal range, may be related to the progression of NAFLD and some typical features of AIH. These results corroborate the importance of encouraging change in eating habits and physical exercise for the control of chronic diseases, including the AIH. To avoid possible errors in diagnosis of AIH, we suggest the inclusion of anthropometric variables in the criteria for diagnosis of AIH, punctuating ...

A obesidade é caracterizada pelo excesso de gordura presente no tecido adiposo e em outros órgãos e está intimamente ligada à RI e outros componentes da Síndrome Metabólica. O excesso de gordura nos hepatócitos atua como um órgão endócrino que libera citocinas inflamatórias e aumenta o recrutamento de linfócitos (células de defesa). Quando a tolerância imunológica é reduzida por esse processo, podemos observar o desenvolvimento de doenças autoimunes. Segundo dados recentes, os lipídios estão especificamente envolvidos na degradação da tolerância hepática, porém mais estudos são necessários para compreender a interação entre a gordura, o sistema imunológico e a esteatose. Nosso objetivo foi estudar a inflamação e a autoimunidade na doença hepática gordurosa não alcoolica (DHGNA) e verificar se a presença do estado inflamatório poderia representar fator contributivo para a presença de marcadores de Hepatite Autoimune (HAI). Tratou-se de um estudo observacional, prospectivo, transversal e descritivo. Foram incluídos 53 sujeitos e realizadas avaliações médicas e nutricionais, exames bioquímicos e biópsia hepática. Separamos a população em dois grupos para análise: CMAI (com marcadores de HAI) e SMAI (sem marcadores de HAI). Encontramos em 58,5% dos sujeitos pelo menos um tipo de autoanticorpo sugestivo de HAI. Não ocorreram diferenças estatisticamente significantes entre os grupos nas variáveis estudadas. Ao aplicarmos o escore da International Group Autoimmune Hepatitis (IGAIH), encontramos um caso com diagnóstico definitivo de HAI. Observamos que a gordura corporal, circunferência abdominal e circunferência do pescoço, quando acima dos valores de normalidade, podem estar relacionadas com a progressão da DHGNA e com algumas características típicas da HAI. Estes resultados corroboram a importância de incentivar a mudança dos hábitos alimentares e a prática de ...
Keywords: Esteatose hepática; Figado - Doenças - Diagnostico; Hepatite; Obesidade; Tecido adiposo; Síndrome metabólica; Exercícios físicos; Fatty Liver